Nasionalisme ekonomi Indonesia dalam era kompetisi global - Syafaruddin Alwi (Universitas Islam Indonesia, 1999)
However, what we call corruption and nepotism (KKN) is a disastrous mixture to the development. Indonesia has proved it. Many people agree that the crisis has been faced by the Indonesian nowadays was caused by the corruption, collusion and nepotism (KKN) practiced by the New Order. As KKN is proved as an obstacle of the Indonesian development, KKN would also be an obstacle factor for Indonesia in entering globalization and trade liberalization.